Studi Kasus Repeat (Pengulangan) Radiograf dengan Modalitas Digital Radiography (DR) di Instalasi Radiologi RSUD Dr. Soehadi Prijonegoro Sragen - Yunita Yunita; Ayu Mahani; Muhammad Za'im (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Repeat analysis is a systematic method for analyzing radiographic images repeatedly to identify and reduce errors in digital processing. This method is part of the quality assurance (QA) and quality control (QC) program which aims to ensure optimal quality radiographic results. According to the Decree of the Minister of Health Number 129/Menkes/SK/II/2008 concerning the standard for repeat radiographic images <2%. This study aims to determine the factors that cause repeat photos and how to prevent repeat photos at Dr. Soehadi Prijonegoro Sragen Hospital. This research method uses qualitative with a case study approach to analyze repeat radiographs using Digital Radiography (DR) at the Radiology Installation of Dr. Soehadi Prijonegoro Sragen Hospital. The study was conducted from September 2024 to March 2025. The population includes all radiographic images with DR modality, while the sample is the result of repeat radiographic images. Data were collected through direct observation, interviews with three radiographers and one radiology specialist, and documentation. The average percentage of repeat X-ray photos on digital radiography modality in October 2024 was 1954 examinations with 122 repeats with a percentage of 6.24%, in November 2024 was 2206 examinations with 70 repeats with a percentage of 3.17%, in December 2024 was 2622 examinations with 16 repeats with a percentage of 0.61%. The percentage of repeats on digital radiography (DR) modality that occurred at Dr. Soehadi Prijonegoro Sragen Hospital exceeded the standards set by the Minister of Health with repeat results> 2% in October and November 2024. The factors causing repeats are due to positioning, patient movement, exposure factors, artifacts and equipment. The suggestion to minimize repeats that occur is to increase the accuracy of the radiographer in conducting the examination.